Osseous impingement occurs early in flexion in cam-type femoroacetabular impingement: a 4D CT model. Issue 4 (April 2017) - Fernquest, S.; Arnold, C.; Palmer, A.; Broomfield, J.; Denton, J.; Taylor, A.; Glyn-Jones, S.
Abstract : Aims: The aim of this study was to examine the real time in vivo kinematics of the hip in patients with cam-type femoroacetabular impingement (FAI). Patients and Methods: A total of 50 patients (83 hips) underwent 4D dynamic CT scanning of the hip, producing real time osseous models of the pelvis and femur being moved through flexion, adduction, and internal rotation. The location and size of the cam deformity and its relationship to the angle of flexion of the hip and pelvic tilt, and the position of impingement were recorded. Results: In these patients with cam-type FAI, there was significant correlation between the alpha angle and flexion to the point of impingement (mean 41.36°; 14.32° to 57.95°) (R = -0.5815 and p = < 0.001). Patients with a large cam deformity (alpha angle > 78°) had significantly less flexion to the point of impingement (mean 36.30°; 14.32° to 55.18°) than patients with a small cam deformity (alpha angle 60° to 78°) (mean 45.34°; 27.25° to 57.95°) (p = < 0.001). Conclusion: This study has shown that cam-type impingement can occur early in flexion (40°), particularly in patients with large anterior deformities. These patients risk chondrolabral damage during routine activities such as walking, and going up stairs. These findings offer important insights into the cause of the symptoms, the mechanisms of screening and the forms of treatment available for these patients. Cite this article: Bone Joint J 2017;99-B(4 Supple B):41–8.